Mainstreaming Politics Gendering Practices and Feminist Theory - Bacchi, Carol (University of Adelaide Press, 2010)
This book offers an innovative rethinking of policy approaches to 'gender equality' and of the process of social change. It brings several new chapters together with a series of previously published articles to reflect on these topics. A particular focus is gender mainstreaming, a relatively recent development in equality policy in many industrialised and some industrialising countries, as well as in large international organisations such as the World Bank, the International Monetary Fund and the International Labour Organization. The book draws upon poststructuralist organisation and policy theory to argue that it is impossible to 'script' reform initiatives such as gender mainstreaming. As an alternative it recommends thinking about such policy developments as fields of contestation, shaped by on-the-ground political deliberations and practices, including the discursive practices that produce specific ways of understanding the 'problem' of 'gender inequality'. In addition to the new chapters Bacchi and Eveline produce brief introductions for each chapter, tracing the development of their ideas over four years. Through these commentaries the book provides exciting insights into the complex processes of collaboration and theory generation. Mainstreaming Politics is a rich resource for both practitioners in the field and for theorists. In particular it will appeal to those interested in public policy, public administration, organisation studies, sociology, comparative politics and international studies.